(3JdNjU cJH CQSWh aj UfGYI GdefWbs
(3ChdgG (B:s
(3GdZQV ai gPG Gdbhd JdNjU GdeYGfi GdJi JVefJgG cJH CQSWh ai UfGYI GdefWb s
(3BNQgG (B:s
(3hbhI GdYbd ddeHGOF GfbVi Ke JdNjU GdebGdI GdKGfjI ef cJGH GdHQgGf hGddg jgOi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(375) s
Keywords: (3GdadSaI hGdefWbs